2011
DOI: 10.1353/pbm.2011.0015
|View full text |Cite
|
Sign up to set email alerts
|

Classification, Disease, and Diagnosis

Abstract: Classification shapes medicine and guides its practice. Understanding classification must be part of the quest to better understand the social context and implications of diagnosis. Classifications are part of the human work that provides a foundation for the recognition and study of illness: deciding how the vast expanse of nature can be partitioned into meaningful chunks, stabilizing and structuring what is otherwise disordered. This article explores the aims of classification, their embodiment in medical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 64 publications
1
59
0
15
Order By: Relevance
“…Another influence may stem from the iterative relationship between medicalisation and diagnosis that is continually evolving (Jutel, 2011). The concepts of diagnosis and medicalisation are inherently linked, nevertheless they are also very different in that entwined within medicalisation is the concept of pharmaceuticalisation (Williams, Gabe, and Davis, 2008; Williams, Martin, and Gabe, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another influence may stem from the iterative relationship between medicalisation and diagnosis that is continually evolving (Jutel, 2011). The concepts of diagnosis and medicalisation are inherently linked, nevertheless they are also very different in that entwined within medicalisation is the concept of pharmaceuticalisation (Williams, Gabe, and Davis, 2008; Williams, Martin, and Gabe, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Classifying diseases into groups determines the response that should be applied in presence of a disease classified within a certain group [10]. If this classification is modernized incorporating the known or inferred disease molecular information, the classification would not only provide the classical structure built on disease physiology, but also provide insight about the associations between disease groups to specific diagnostics and treatments [8], [11].…”
Section: Related Workmentioning
confidence: 99%
“…As such, they reveal the constellation of interests, beliefs, and power relations that result in defining the human body (Conrad & Schneider, 1992). Whilst early medicalization models (Freidson, 1972;Illich, 1974;Zola, 1972) highlighted the top-down, social control function of medicine where, for instance doctors increased markets, legitimated their authority, and controlled patients, subsequent models have included a more nuanced set of representational practices (Atkinson, 1995;de Swann, 1990;Riessman, 1983;Bryant 2011). Jutel (20112013;2014) provides the example of 'boundary transgression' in influenza where diagnosis shifts across social, clinical, epidemiological, lay and professional contexts, each with a different representation of the same medical reality.…”
Section: Social Representations Theorymentioning
confidence: 99%
“…Freidson (1972) has shown that the ability to classify disease anchors professional status within medicine (Jutel 2011), so that the clinician is the final arbiter of the diagnostic label.…”
Section: Introductionmentioning
confidence: 99%